Chapter Introduction Why This Book and Why Now - Dorner, Lisa M. (Taylor & Francis, 2023)
Dual language bilingual programs aim to develop bilingualism, biliteracy, and sociocultural competence while meeting grade-level academic standards. There are at least four dual language bilingual education (DLBE) program models, which are traditionally defined by the student groups they imagine serving. One of these groups is transnational and racialized language learners who are, more often than not, otherwise marginalized in US schools. Well-implemented DLBE programs, with their roots in the historical and political fight for civil and educational rights for children who speak languages other than English, have been shown to be demonstrably effective for this group. Unfortunately, not all programs are well implemented, and they exist in spaces with colonial and racist histories, as pointed out by Guadalupe Valdés's cautionary note decades ago. Even when DLBE programs are designed specifically for racialized and transnational language learners, research has documented persistent challenges to equity.